2022
DOI: 10.1177/00220345221138525
|View full text |Cite
|
Sign up to set email alerts
|

Fibromodulin, a Multifunctional Matricellular Modulator

Abstract: Fibromodulin (FMOD) is an archetypal member of the class II small leucine-rich proteoglycan family. By directly binding to extracellular matrix structural components, such as collagen and lysyl oxidase, FMOD regulates collagen cross-linking, packing, assembly, and fibril architecture via a multivalent interaction. Meanwhile, as a pluripotent molecule, FMOD acts as a ligand of various cytokines and growth factors, especially those belonging to the transforming growth factor (TGF) β superfamily, by interacting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Subsequently, a literature review was performed on these genes, revealing that FMOD serves as a multifunctional regulator of the extracellular matrix, exerts anti-inflammatory effects, and facilitates angiogenesis. 26 The results of KEGG enrichment analysis revealed that TGF-β signaling was the downstream pathway of FMOD, and the correspondence between the FMOD and TGF-β signaling pathways is shown in the KEGG chord diagram (Fig. 3E and F).…”
Section: Resultsmentioning
confidence: 87%
“…Subsequently, a literature review was performed on these genes, revealing that FMOD serves as a multifunctional regulator of the extracellular matrix, exerts anti-inflammatory effects, and facilitates angiogenesis. 26 The results of KEGG enrichment analysis revealed that TGF-β signaling was the downstream pathway of FMOD, and the correspondence between the FMOD and TGF-β signaling pathways is shown in the KEGG chord diagram (Fig. 3E and F).…”
Section: Resultsmentioning
confidence: 87%
“…As a member of the leucine-rich small proteoglycan family, fibromodulin has an important role in collagen fibril production. Recently, a study has reported that fibromodulin can regulate collagen cross-linking, accumulation, and assembly and the collagen fibril structure through multivalent interactions . In addition, its interaction with lysyl oxidase helps to regulate the ECM composition, thus providing a relaxed environment to regulate cell renewal .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study has reported that fibromodulin can regulate collagen cross-linking, accumulation, and assembly and the collagen fibril structure through multivalent interactions. 31 In addition, its interaction with lysyl oxidase helps to regulate the ECM composition, thus providing a relaxed environment to regulate cell renewal. 32 In other words, fibromodulin profoundly influences the structural composition of the ECM.…”
Section: Collagenmentioning
confidence: 99%
“…As an ECM protein, Fibromodulin (FMOD) plays a role in multiple cellular biological events, including ECM remodeling, collagen fibrogenesis, dedifferentiation, and inflammation. 19 , 20 Beyond that, current evidence suggests that FMOD acts as diagnostic and prognostic biomarkers in cancers and exerts oncogenic roles by regulating cell apoptosis, angiogenesis, and migration. 20 , 21 Mayr and colleagues have reported that FMOD is a tumor-associated antigen in chronic lymphocytic leukemia via facilitating the expansion of specific CD8 + autologous T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%